How Does One Become a Greek, or On the Panhellenism in Xenophon’s Anabasis - Jaskelevičius, Alius (Literatūra, 2018)
[abstract in English; full article and abstract in Lithuanian]Xenophon’s Anabasis is an extremely rich and multilayered piece of writing with a variety of themes and subthemes. Scholars do not agree as to which theme or subtheme could be a key to reading the work. Therefore, they analyze every theme separately depending on which of them they consider to be most important one. According to one of the interpretations, Xenophon implicitly invites the Greeks to a Panhellenic expedition against Persia, the weakness of which is clearly demonstrated by the mobile Greek mercenary army with Xenophon as its leader. Moreover, it is added that Xenophon is simultaneously promoting his own qualities as a possible leader of this army. The paper explores this Panhellenic aspect of Anabasis from a different point of view – by analyzing the phenomenon of an army as an organized and self-organizing unit as well as its problems. By raising questions about the structure, organization and subordination of the army, the question of Panhellenism is touched upon. The paper also deals with the questions of under what conditions and circumstances the Panhellenism is possible and, especially, how is it possible in such an isolated unit as the Ten Thousand Army
Keywords: Xenophon, Cyrus, panhellenism, identity